2009
DOI: 10.1179/174313209x385617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium, MK-801 and combination of magnesium and MK-801 on blood–brain barrier permeability and brain edema after experimental traumatic diffuse brain injury

Abstract: The present data demonstrate that treatment with magnesium, MK-801 and combination of magnesium and MK-801 can reduce formation of brain edema and can help restore BBB permeability after experimental diffuse brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…29 A previous study demonstrated that early intervention with Cerebrolysin reduces the BBB permeability and diminishes brain edema and other brain pathology, which contributes to recovery of sensorimotor function after TBI induced by a stab cerebral injury. 56 In the present study, Cerebrolysin treatment significantly increased the percentage of FITC-dextran-perfused vessels in the brain cortex, indicating that Cerebrolysin enhances the microvascular patency of the brain after CHI.…”
Section: Discussionmentioning
confidence: 99%
“…29 A previous study demonstrated that early intervention with Cerebrolysin reduces the BBB permeability and diminishes brain edema and other brain pathology, which contributes to recovery of sensorimotor function after TBI induced by a stab cerebral injury. 56 In the present study, Cerebrolysin treatment significantly increased the percentage of FITC-dextran-perfused vessels in the brain cortex, indicating that Cerebrolysin enhances the microvascular patency of the brain after CHI.…”
Section: Discussionmentioning
confidence: 99%
“…This could imply that, in addition to influencing hemostasis, Mg might have possible neuroprotective effects for patients with ICH 24. Preclinical data suggest that Mg exhibits multiple complementary neuroprotective mechanisms, including inhibition of glutamate release,25 restoration of blood‐brain barrier integrity, decrease in brain edema,26 and noncompetitive antagonism of N‐methyl‐ d ‐aspartate receptor activation via blockage of voltage‐dependent calcium channels 24, 27. Moreover, the antihypertensive effect of Mg could be protective in patients with ICH 24…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that magnesium improves functional outcome following blood brain barrier disruption and decrease brain edema (13). Studies on the effect of magnesium or hypertonic saline in experimental models commonly applied intraperitoneal or intra-arterial way of drug administration (13,14). However, the efficacy of intraventricular hypertonic saline and magnesium on brain cell damage in severe head injury has not been evaluated yet.…”
Section: Introductionmentioning
confidence: 99%